Geographical distribution of Discocyrtus prospicuus (Arachnida: Opiliones: Gonyleptidae): Is there a pattern? - Acosta, Luis Eduardo (2011)
The environmental constraints determining the distribution of the harvestman Discocyrtus prospicuus in Argentina andUruguay are addressed. Habitat observations across the entire range (Río de la Plata-Atlantic coast area; Córdoba sierras;northwestern Argentina) are provided. Previous published localities (verified for accuracy), new records and bioclimaticpredictors were used to characterize the species bioclimatic profile and to build predictive distributional models with BIOCLIMand MAXENT algorithms. Relative importance of each bioclimatic variable in the final models is assessed. It wasdetermined that D. prospicuus is primarily a gallery forest dweller, with preferred climate temperate to temperate-cold;variables related to thermic uniformity rank among the most influential. Results consistently support the alleged yungas-Mesopotamian disjunction; but the link between the Río de la Plata and Córdoba sierras areas shows disagreement betweenmethods (predicted continuous with BIOCLIM, separate with MAXENT). It is suggested that the need for constant airhumidity (favored in the core area by its proximity to large rivers and the seacoast) and competitive exclusion with congenerD. testudineus may represent additional limiting factors. Some observations on the species tolerance to human activityare also given.